PiT2 deficiency prevents increase of bone marrow adipose tissue during skeletal maturation but not in OVX-induced osteoporosis - Frangi, Giulia; Guicheteau, Marie; Jacquot, Frederic; Pyka, Grzegorz; Kerckhofs, Greet; Feyeux, Magalie; Veziers, Joëlle; Guihard, Pierre; Halgand, Boris; Sourice, Sophie; Guicheux, Jérôme; Prieur, Xavier; et al. (Frontiers in Endocrinology, 2022)
The common cellular origin between bone marrow adipocytes (BMAds) and osteoblasts contributes to the intimate link between bone marrow adipose tissue (BMAT) and skeletal health. An imbalance between the differentiation ability of BMSCs towards one of the two lineages occurs in conditions like aging or osteoporosis, where bone mass is decreased. Recently, we showed that the sodium-phosphate co-transporter PiT2/SLC20A2 is an important determinant for bone mineralization, strength and quality. Since bone mass is reduced in homozygous mutant mice, we investigated in this study whether the BMAT was also affected in PiT2-/- mice by assessing the effect of the absence of PiT2 on BMAT volume between 3 and 16 weeks, as well as in an ovariectomy-induced bone loss model. Here we show that the absence of PiT2 in juveniles leads to an increase in the BMAT that does not originate from an increased adipogenic differentiation of bone marrow stromal cells. We show that although PiT2-/- mice have higher BMAT volume than control PiT2+/+ mice at 3 weeks of age, BMAT volume do not increase from 3 to 16 weeks of age, leading to a lower BMAT volume in 16-week-old PiT2-/- compared to PiT2+/+ mice. In contrast, the absence of PiT2 does not prevent the increase in BMAT volume in a model of ovariectomy-induced bone loss. Our data identify SLC20a2/PiT2 as a novel gene essential for the maintenance of the BMAd pool in adult mice, involving mechanisms of action that remain to be elucidated, but which appear to be independent of the balance between osteoblastic and adipogenic differentiation of BMSCs.